Innovation, value and reimbursement in radiation and complex surgical oncology: Time to rethink. (April 2022) - Borras, Josep M.; Corral, Julieta; Aggarwal, Ajay; Audisio, Riccardo; Espinas, Josep Alfons; Figueras, Josep; Naredi, Peter; Panteli, Dimitra; Pourel, Nicolas; Prades, Joan; Lievens, Yolande
Highlights: High variability in reimbursement across countries in radiation and surgical oncology. Reimbursement should differentiate proven evidence-based interventions from emerging innovation. Criteria for reimbursement of proven evidence should be based on episode of care. For emerging innovation, coverage with evidence development should be considered. Abstract: Background and purpose: Complex surgery and radiotherapy are the central pillars of loco-regional oncology treatment. This paper describes the reimbursement schemes used in radiation and complex surgical oncology, reports on literature and policy reviews. Material and methods: A systematic review of the literature of the reimbursement models has been carried out separately for radiotherapy and complex cancer surgery based on PRISMA guidelines. Using searches of PubMed and grey literature, we identified articles from scientific journals and reports published since 2000 on provider payment or reimbursement systems currently used in radiation oncology and complex cancer surgery, also including policy models. Results: Most European health systems reimburse radiotherapy using a budget-based, fee-for-service or fraction-based system; while few reimburse services according to an episode-based model. Also, the reimbursement models for cancer surgery are mostly restricted to differences embedded in the DRG system and adjustments applied to the fees, based on the complexity of each surgical procedure. There is an enormous variability in reimbursement across countries, resulting in different incentives and different amounts paid for the same therapeutic strategy. Conclusion: A reimbursement policy, based on the episode of care as the basic payment unit, is advocated for. Innovation should be tackled in a two-tier approach: one defining the common criteria for reimbursement of proven evidence-based interventions; another for financing emerging innovation with uncertain definitive value. Relevant clinical and economic data, also collected real-life, should support reimbursement systems that mirror the actual cost of evidence-based practice.